Bargaining with patriarchy: Former female coaches' experiences and their decision to leave collegiate coaching - Kamphoff, C. S. (Research Quarterly for Exercise and Sport, 2010)
The purpose of this study was to better understand the experiences of former female coaches and their decision to terminate their careers. A feminist perspective and mixed-methods (surveys and interviews) were used to allow for a richer understanding of their experiences. The survey findings, which included 121 former female coaches, suggest that time and family commitments were the main reasons they left coaching. Also, a small number (18%) left coaching for reasons such as opportunity for promotion. Six women from the survey sample were individually interviewed. Through a descriptive analytic strategy and indexing process (Creswell, 1998), three general themes emerged: (a) gender disparities in women's work, (b) technical demands of coaching, and (c) college coaching and normalized sexualities. Overall, the interview findings confirmed the open-ended responses on the survey and described gender discrimination, the centrality of male coaches, and rampant homophobia in U.S. collegiate coaching. In addition, some female coaches discussed perceptions of conflict between working as a coach and motherhood, or women with children as being "distracted" by motherhood. Collectively, the survey and interview results revealed that women have multiple, complex, and overlapping reasons for leaving collegiate coaching.